Polyethylene single bubble insulation capability in reducing cooling load of a lecture hall - Muhieldeen, Mohammed W. (2011)
Many researchers have done different studies on energy consumption, and its effects on thermal comfort, while this is important the amount of energy conservation was not done properly. The objective of this work is to study the potential of polyethylene aluminum single bubble as an insulator material for a lecture hall D.K.1 (15m×12m×6.6m) at Universiti Putra Malaysia. The lecture hall has an external wall facing North 112East. The methodology involved taking measurementsof air temperature, air velocity, relative humidity, and number of students for the month of April 2009 as input parameters for the three dimensional computational fluid dynamics (CFD) code name FLUENT 6.3 to determine potential reduction in temperature inside the lecture hall; the CFD results prior to further simulation work was checked against published literature.Results from simulation work showed that a reduction temperature of 2.7 ºC was possible for the lecture hall. An experiment was conducted on two adjacent small rooms (5m×2m×2.8m each) with and without insulation material on the external wall facing the same orientation as the lecture hall to verify the difference in temperature when using the insulation material. The measurements of air temperature and relative humidity were conducted using a far infrared thermometer and VELOMETER AVM 440 respectively. The measurements were conducted on two different days from 9am to 3 pm. Results showed it was possible to get 3 ºC temperature reductions when using the polyethylene aluminiumsingle bubble insulator, and the calculation estimated showed potential saving of RM 1453.5 for one day. The capability of using polyethylene single bubble insulation is reducing cooling load by 2.7 ºC and reduction of operation cost by RM 1453.5 per day for a 80 people lecture hall.